1983
DOI: 10.1254/jjp.33.1233
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals-induced changes in mesenteric microvascular dimensions in the anesthetized cat.

Abstract: Abstract-Effect of free radicals on microvascular dimensions was studied in anes thetized cat intestinal mesentery. Generation of free radicals by xanthine oxidase, acting on endogenous substrates (e.g., xanthine, hypoxanthine), produced sustained vasodilation at pH 7.4 or at pH 6.6. These effects were reversed by superoxide dismutase (SOD), a superoxide radical ('02-) scavenger, at pH 7.4, and by SOD plus hydroxyl radical ('OH) scavenger d-mannitol at pH 6.6. These findings suggest that the sustained vasodila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Kontos and co‐workers (1984) showed that free radicals produced an irreversible vasodilatation in pial arterioles of cats, in vivo. Similar findings were obtained by Okabe et al (1983) in the cat mesenteric microcirculation. Xanthine oxidase‐derived radicals were shown by Wolin and Belloni (1985) to decrease tension in noradrenaline (NA) precontracted vessel rings.…”
Section: Introductionsupporting
confidence: 89%
“…Kontos and co‐workers (1984) showed that free radicals produced an irreversible vasodilatation in pial arterioles of cats, in vivo. Similar findings were obtained by Okabe et al (1983) in the cat mesenteric microcirculation. Xanthine oxidase‐derived radicals were shown by Wolin and Belloni (1985) to decrease tension in noradrenaline (NA) precontracted vessel rings.…”
Section: Introductionsupporting
confidence: 89%
“…The other pharmacological action of eugenol-induced 02 production, vasodi lation, is considered apart from the direct action of the drug, because exogeneous 02 dilates cat mesentric blood vessels (24).…”
Section: Inductionmentioning
confidence: 99%